Nuclear Medicine Applications in Pediatric Musculoskeletal Diseases: The Added Value of Hybrid Imaging - Parisi, Marguerite T.; Iyer, Ramesh S.; Stanescu, A. Luana (Seminars in Musculoskeletal Radiology, 2018)
The introduction of diphosphonates in the 1970s revolutionized not only nuclear medicine but musculoskeletal imaging as well, providing functional assessment of entities such as osteomyelitis, trauma, and osseous metastatic disease. Although rarely the first-line imaging modality used today, nuclear medicine procedures continue to play a pivotal role in the evaluation of musculoskeletal diseases in children, providing whole-body assessment of disease involvement. More recently, the introduction of technologies such as single-photon emission computed tomography/computed tomography (SPECT/CT), as well as newer positron-emitting tracers such as 18fluorine-fluorodeoxyglucose and sodium 18F-fluorine, particularly when combined with CT (positron emission tomography/CT), have injected new life into the older established techniques and expanded the application of nuclear medicine imaging into new arenas. This article discusses the utility of standard nuclear medicine procedures as they apply to children with musculoskeletal disorders, focusing on the added value of and indications for SPECT/CT. Subsequently, we discuss the expanding role of positron-emitting agents in infection, trauma, and for the diagnosis, staging, and therapeutic response monitoring of children with malignant bone and soft tissue tumors. Differences between disease processes encountered in children as compared with adults are discussed; developmental variants that can, but should not, be confused with disease are illustrated. The need for pediatric-specific protocols is addressed.
Keywords: pediatric; musculoskeletal; nuclear medicine; SPECT/CT; PET/CT